PERANCANGAN LAPAS DENGAN PENDEKATAN BIOFILIK BERBASIS PEMASYARAKATAN DI KARAWANG BARAT - Fanny Fanny; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2022)
The way of life in almost all countries is regulated by law. A person who is found guilty of a crime and convicted by a court is called a convict and the convict who will carry out a sentence that causes pain due to the loss of independence is called a prisoners. However, in addition to carrying out the crime, it is necessary to guide the convict to repent and educate so that he becomes a useful member of Indonesian society. Thus, the purpose of imprisonment is correctional, which implies that not only the community is protected against repeated crimes by the convict, but also protected by a banyan tree and given life provisions. So that he becomes a useful member of the Indonesian social community. The purpose of this design as an effort to present a healthy and beautiful prison to achieve the coaching process in accordance with the goals of the correctional institution and to question the extent to which a prison typology can be developed to produce a new typology while maintaining an active typology that can answer the challenges/problems that cause delays in the coaching process. prisoners. By developing the concept of biophilic for healing in a program that will be carried out by prisoners, namely focusing on the five senses (therapy through the senses of sight, touch, smell and hearing); coaching and education; and agriculture (plantation and agriculture) as well as incorporating biophilic elements into the basic form of the building mass. Keywords: Biophilic; Prison; Prisoners; Typology AbstrakTata cara menjalankan kehidupan di hampir seluruh negara diatur oleh hukum. Orang yang didakwa bersalah atas sebuah kejahatan dan dihukum oleh pengadilan disebut terpidana dan terpidana akan menjalankan pidana yang menimbulkan rasa derita karena hilangnya kemerdekaan disebut narapidana. Namun selain menjalankan pidana perlu pembimbingan bagi terpidana agar bertobat dan mendidik supaya ia menjadi seorang anggota masyarakat Indonesia yang berguna. Sehingga, tujuan pidana penjara adalah permasyarakatan, yang mengandung makna bahwa tidak hanya masyarakat yang diayomi terhadap diulanginya perbuatan jahat oleh terpidana, melainkan juga diayomi oleh pohon beringin dan diberikan bekal hidup. Sehingga menjadi seorang anggota masyarakat sosial Indonesia yang berguna. Tujuan dari perancangan ini sebagai bentuk upaya menghadirkan lapas yang sehat dan asri untuk tercapainya proses pembinaan sesuai dengan tujuan Lembaga permasyarakatan serta mempertanyakan sejauh mana suatu tipologi penjara dapat dikembangkan untuk menghasilkan tipologi baru dengan tetap mempertahankan tipologi aktifnya yang dapat menjawab tantangan / masalah penyebab terhambatnya proses pembinaan narapidana. Dengan mengembangkan konsep biophilic for healing dalam program yang akan dilaksanakan oleh narapidana yaitu berfokuskan pada pancaindra (terapi melalui indra penglihatan, peraba, penciuman dan pendengaran); pembinaan dan pendidikan; dan argrikultur (perkebunan dan pertanian) serta memasukan unsur biophilic ke dalam bentuk dasar massa bangunan.